Food consumption of univesity students according to the food guide for the Brazilian population (Research, Society and Development, 2021)
Introduction: The process of transition from high school to college influences on proper nutrition, due to the environment in which they are inserted, causing beneficial foods not to be consumed due to time, increased responsibilities, absence of parents or guardians, making room for a high consumption of ultra-processed and, consequently, causing a decrease in the consumption of fruits, vegetables and greens. Objective: To evaluate the eating habits of college students entering the first three semesters of the nutrition course in a private institution of higher education, to determine the relationship between poor diet and socioeconomic factors, and to identify whether it is associated with the routine and the absence of parents. Methods: This research aims to carry out a quantitative, analytical, cross-sectional study with undergraduate students of the Nutrition course at a private institution of higher education. Eating practices were obtained through the scale developed and validated by Gabe and Jaime in 2019. Sociodemographic characteristics, lifestyle habits and health conditions were evaluated. Data analysis will comprise by frequency distribution and bivariate analysis through the chi-square test. Results and conclusion: In view of the results presented it was possible to conclude that the number of female students is higher, in addition the aspects observed showed that the sociodemographic variables, living habits and health conditions of students had no influence on the dietary practices of the surveyed population, with the exception of health assessment and change of diet after entering college, which showed association with the classification of food adequacy.